2015
DOI: 10.1186/s12885-015-1874-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fluorescence–based multiplex genotyping method for simultaneous determination of human papillomavirus infections and viral loads

Abstract: BackgroundPersistent high-risk human papillomavirus (HPV) infection is correlated with an increased risk of developing intraepithelial lesion or malignancy (NILM). The aims of the current study is to establish a method named BioPerfectus Multiplex Real Time (BMRT) HPV assay for simultaneous typing and quantifying HPVs, and to evaluate it by comparison with HPV GenoArray test and PCR-sequencing method, as well as histological status.MethodsA total of 817 cervical specimens were evaluated by BMRT method and HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…HPV viral load in serial measuring could predict cervical lesion progression [22]. The risk of CC and HSIL increases with the viral load, which could triage HR-HPV-positive women [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…HPV viral load in serial measuring could predict cervical lesion progression [22]. The risk of CC and HSIL increases with the viral load, which could triage HR-HPV-positive women [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported 24 the BioPerfectus Multiplex Real-Time PCR (BMRT) assay, which was a newly developed, highly automated approach for quantifying viral loads for 14 HR-HPV types. This method provides an absolute quantitative measure of individual types with normalization according to the amount of human DNA.…”
Section: Introductionmentioning
confidence: 99%
“…This method provides an absolute quantitative measure of individual types with normalization according to the amount of human DNA. 24 , 25 In order to confirm that type-specific HPV viral loads correlate with the grade of cervical lesions and determine whether the type-specific HPV viral load is a viable risk identification tool for ≥HSIL in HR-HPV–positive women, the present study analyzed type-specific viral loads of 14 HR-HPV types using the BMRT assay in a large-scale clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from biopsy samples using QIAamp DNA mini kit (Qiagen, Germany) according to the manufacturer's instructions. PCR was performed using the fluorescence-based multiplex HPV DNA genotyping kit (Bioperfectus Ltd., China) that is designed to identify 19 high-risk or possibly carcinogenic HPV types (16,18,26,31,33,35,39,45,51,52,53,56,58,59, 66, 67, 68, 73, and 82) and 3 low-risk HPV types (6, 11, and 81) [16]. Results were analyzed using the Perfectus Software v1.0 (Bioperfectus Ltd., China).…”
Section: Hpv Genotyping On Biopsy Samplesmentioning
confidence: 99%